Phosphorylation site S122 in estrogen receptor alpha has a tissue-dependent role in female mice - Claes Ohlsson; Karin L. Gustafsson; Helen H. Farman; Petra Henning; Vikte Lionikaite; Sofia Movérare‐Skrtic; Klara Sjögren; Anna E. Törnqvist; Annica Andersson; Ulrika Islander; Angelina I. Bernardi; Matti Poutanen; et al. (WILEY, 2025)
Estrogen treatment increases bone mass and reduces fat mass but is associated with adverse effects in postmenopausal women. Knowledge regarding tissue-specific estrogen signaling is important to aid the development of new tissue-specific treatments. We hypothesized that the posttranslational modification phosphorylation in estrogen receptor alpha (ER alpha) may modulate ER alpha activity in a tissue-dependent manner. Phosphorylation of site S122 in ER alpha has been shown in vitro to affect ER alpha activity, but the tissue-specific role in vivo is unknown. We herein developed and phenotyped a novel mouse model with a point mutation at the phosphorylation site 122 in ER alpha (S122A). Female S122A mice had increased fat mass and serum insulin levels but unchanged serum sex steroid levels, uterus weight, bone mass, thymus weight, and lymphocyte maturation compared to WT mice. In conclusion, phosphorylation site S122 in ER alpha has a tissue-dependent role with an impact specifically on fat mass in female mice. This study is the first to demonstrate in vivo that a phosphorylation site in a transactivation domain in a nuclear steroid receptor modulates the receptor activity in a tissue-dependent manner.